2018
DOI: 10.3390/ijerph16010045
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficacy of Government Spending on Air Pollution Control: A Case Study from Beijing

Abstract: The reform and opening up of the Chinese economy over the last 40 years has led to rapid economic development. However, with the rapid expansion of the economy, increasingly serious air pollution is apparent. In order to control urban air pollution effectively, Chinese governments at all levels have invested large sums every year. However, it has become a difficult issue which influences public government decisions with respect to how and according to what standard to distribute financial funds so as to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
(18 reference statements)
1
8
0
Order By: Relevance
“…This is similar to the conclusion from Bostan et al [38], who also found a significant effect of public expenditures on the decrease of pollution. Also similar observation was found by Xie and Wang [44]-according to their analysis government financial input has an obvious influence on the improvement of air quality, especially when they considered inhalable particulate matter (PM 2.5 , PM 10 ), sulfur dioxide (SO 2 ), and nitrogen dioxide (NO 2 ) in the year 2006 to 2015 in China. Based on our results, we can conclude that the EU environment policy is an efficient tool to struggle with PM 2.5 .…”
Section: Resultssupporting
confidence: 76%
“…This is similar to the conclusion from Bostan et al [38], who also found a significant effect of public expenditures on the decrease of pollution. Also similar observation was found by Xie and Wang [44]-according to their analysis government financial input has an obvious influence on the improvement of air quality, especially when they considered inhalable particulate matter (PM 2.5 , PM 10 ), sulfur dioxide (SO 2 ), and nitrogen dioxide (NO 2 ) in the year 2006 to 2015 in China. Based on our results, we can conclude that the EU environment policy is an efficient tool to struggle with PM 2.5 .…”
Section: Resultssupporting
confidence: 76%
“…While the rising concerns of the individuals were mostly determined by the impacts of environment degradation on their health and their quality of life, governments and researchers had a much larger perspective looking to determine also specific correlations between environment condition and other economic indicators. In this regard, literature includes studies on the relationships between environment and economic growth [1][2][3][4][5][6][7][8], taxation [9][10][11][12], government or private expenditures [13][14][15][16] in order to find appropriate solutions for counteracting the process of environment's degradation and to adjust the environmental policies [17][18][19][20][21][22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For the air quality ranking, China was ranked the second-worst, with a score of 18.81, a decrease of 14.15% compared with 10 years ago. 44 From the global perspective, outdoor particularly air pollution resulted in 2.9 million deaths in 2017, which shows an increase of 1.7 million from 1990. This shows that environmental quality in terms of air pollution can influence life expectancy and our empirical estimation may further verify this argument.…”
Section: Introductionmentioning
confidence: 99%
“…According to the ‘Environmental Performance Index’ report in 2014, China was ranked 118th out of 178 countries. For the air quality ranking, China was ranked the second‐worst, with a score of 18.81, a decrease of 14.15% compared with 10 years ago 44 . From the global perspective, outdoor particularly air pollution resulted in 2.9 million deaths in 2017, which shows an increase of 1.7 million from 1990.…”
Section: Introductionmentioning
confidence: 99%